Density functional theory study on the solubilization in water of functionalized single-wall carbon nanotubes - Mananghaya, Michael R. (Animo Repository, 2011)
An important technique to increase the solubility and reactivity carbon nanotube is through functionalization. In this study, the effects of functionalization of some single-walled carbon nanotube (SWCNT) were investigated with the aid of density functional theory (DFT). The SWCNT model used in the study consists of a finite, (5, 0) zigzag nanotube segment containing 60 C atoms with hydrogen atoms added to the dangling bonds of the perimeter carbons. There are three water-dispersible SWCNT used in this study that were functionalized with: (a) formic acid, as a model of carboxylic acid, (b) isophthalic acid, as a model aromatic dicarboxylic acid, and (c) benzenesulfonic acid, as a model aromatic sulfonic acid. Binding energies of the organic radicals to the nanotubes are calculated, as well as the HOMO-LUMO gaps and dipole moments of both nanotube and functionalized nanotubes. Binding was found out to be thermodynamically favorable. The functionalization increases the electrical dipole moments and results in an enhancement in the solubility of the nanotubes in water manifested through favorable changes in the free energies of solvation. This should lower the toxicity of nanotubes and improve their biocompatibility.